3‐[(2, 4‐dimethoxy)benzylidene]‐anabaseine dihydrochloride protects against 6‐hydroxydopamine‐induced parkinsonian neurodegeneration through α7 nicotinic acetylcholine receptor stimulation in rats. Issue 3 (14th December 2012) - Suzuki, Syuuichirou; Kawamata, Jun; Matsushita, Takashi; Matsumura, Akihiro; Hisahara, Shin; Takata, Kazuyuki; Kitamura, Yoshihisa; Kem, William; Shimohama, Shun
Abstract To explore a novel therapy against Parkinson's disease through enhancement of α7 nicotinic acetylcholine receptor (nAChR), we evaluated the neuroprotective effects of 3‐[(2, 4‐dimethoxy)benzylidene]‐anabaseine dihydrochloride (DMXBA; GTS‐21), a functionally selective α7 nAChR agonist, in a rat 6‐hydroxydopamine (6‐OHDA)‐induced hemiparkinsonian model. Microinjection of 6‐OHDA into the nigrostriatal pathway of rats destroys dopaminergic neurons selectively. DMXBA dose dependently inhibited methamphetamine‐stimulated rotational behavior and dopaminergic neuronal loss induced by 6‐OHDA. The protective effects were abolished by methyllycaconitine citrate salt hydrate, an α7 nAChR antagonist. Immunohistochemical study confirmed abundant α7 nAChR expression in the cytoplasm of dopaminergic neurons. These results indicate that DMXBA prevented 6‐OHDA‐induced dopaminergic neuronal loss through stimulating α7 nAChR in dopaminergic neurons. Injection of 6‐OHDA elevated immunoreactivities to glial markers such as ionized calcium binding adaptor molecule 1, CD68, and glial fibrillary acidic protein in the substantia nigra pars compacta of rats. In contrast, these immunoreactivities were markedly inhibited by comicroinjection of DMXBA. Microglia also expressed α7 nAChR in both resting and activated states. Hence, we hypothesize that DMXBA simultaneously affects microglia and dopaminergic neurons and that both actions lead to dopaminergic neuroprotection. The findings that DMXBA attenuates 6‐OHDA‐induced dopaminergic neurodegeneration and glial activation in a rat model of Parkinson's disease raisethe possibility that DMXBA could be a novel therapeutic compound to prevent Parkinson's disease development. © 2012 Wiley Periodicals, Inc.